2019
DOI: 10.1155/2019/1914762
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis for Downlink MIMO-NOMA in Millimeter Wave Cellular Network with D2D Communications

Abstract: Enabling nonorthogonal multiple access (NOMA) in device-to-device (D2D) communications under the millimeter wave (mmWave) multiple-input multiple-output (MIMO) cellular network is of critical importance for 5G wireless systems to support low latency, high reliability, and high throughput radio access. In this paper, the closed-form expressions for the outage probability and the ergodic capacity in downlink MIMO-NOMA mmWave cellular network with D2D communications are considered, which indicates that NOMA outpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In [2], the authors studied the outage probability and the ergodic capacity in downlink MIMO-NOMA at mmWave cellular network with D2D communications. Analytical results indicated that NOMA outperforms time division mul-tiple access (TDMA).…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [2], the authors studied the outage probability and the ergodic capacity in downlink MIMO-NOMA at mmWave cellular network with D2D communications. Analytical results indicated that NOMA outperforms time division mul-tiple access (TDMA).…”
Section: B Related Workmentioning
confidence: 99%
“…, G. Here, CU E(g, k) denotes that the CUE is served by the g-th beam with sequence k in that beam, where |S g | ≥ 1 and S i ∩S j = φ for i = j. According to NOMA, the BS transmits a superimposed signal X g for all K CUEs in the g-th cluster via g-th beam [2] [23], and X g can be expressed as…”
Section: A Noma Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4], the coverage probability, the average number of served users, and the sum rate of NOMA were studied for the cooperative multicast mmWave wireless networks over Nakagami-m fading channels. In [5], the OP and the ergodic capacity (EC) were investigated in downlink MIMO-NOMA mmWave cellular networks with D2D communications over Nakagami-m fading channels. However, the small-scale fading effects in these considered mmWave communication scenarios were modeled by using Nakagami-m fading or some other simplified fadings.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of millimeter wave (mmWave) communication have become the essential technology for Fifth-Generation (5G) and beyond wireless communications systems [7], [8]. Thus, many researchers have been paying attention to the research where NOMA system is integrated with multiple-antenna beamforming techniques in mmWave channel [9]- [13]. By exploiting the degree of freedom in spatial-domain in addition to the advantage of NOMA, groups of users can be supported by NOMA spatially in different beams [5], [6].…”
Section: Introductionmentioning
confidence: 99%